Unique Fixed Point Results via Geraghty Type Contraction with Applications (European Journal of Pure and Applied Mathematics, 2025)
In this research work, using the concept of Banach contraction principle and Geraghty type contractions, some unique fixed point results are established in the context of $μ$-extended fuzzy b-metric spaces. The developed results are applied to ensure the existence of solution to integral equation and non-linear fractional order differential equation.
Keywords: Fixed point results, Geraghty type contraction, fuzzy b-metric spaces, integral equation, fractional differential equation